Effect of Transcranial Direct Current Stimulation in the Treatment of Aphasia after Stroke：A Meta-Analysis - CUI Ying; LI Bo; TIAN Guang (康复学报)
ObjectiveTo evaluate the clinical efficacy of transcranial direct current stimulation (tDCS) in the treatment of aphasia after stroke by meta-analysis.MethodsData were searched from the Chinese databases (China National Knowledge Infrastructure Database, Wanfang Database, China Biology Medicine Database, VIP Database) and English databases (PubMed, Web of Science, Embase and Cochrane Library). The randomized controlled trials (RCTs) of tDCS in the treatment of aphasia after stroke were included, and the retrieval time for each database was from inception to August 2021. The main outcome measures were clinical efficacy, aphasia symptom scores [Western aphasia battery (WAB), picture naming test, communication abilities of daily living (CADL), etc.]. Two researchers conducted literature screening, data extraction and quality evaluation independently according to the inclusion and exclusion criteria. The odds ratio (OR) and 95% confidence interval (CI) were used as the effect indicators for the ranking data and Stata 15 was used for meta-analysis of clinical efficacy; RevMan 5.4 was used to analyze the continuous data by Meta-analysis, and the mean difference (MD) and 95% CI were used as the effect indexes. The statistical heterogeneity was assessed by probability value (P value) and heterogeneity value (I 2 value). The fixed effects model was used when the included studies were homogeneous (I 2≤50%, P≥0.1) , while the random-effects model was used for analysis when the included studies were heterogeneous (I 2>50%, P<0.1).ResultsA total of 16 RCTs with 843 cases were included. The results of meta-analysis showed that, (1) Clinical efficacy: compared with the control group, the clinical effect of the experimental group was higher [OR=3.46, 95% CI (2.30, 5.21), P<0.001]. (2) WAB score: compared with the control group, the WAB- aphasia quotient (WAB-AQ) score of the experimental group was significantly higher [MD=14.06, 95% CI (11.82, 16.29), Z=12.32, P<0.000 01]，WAB-spontaneous language score was significantly higher [MD=2.13, 95% CI (1.32, 2.94), Z=5.17, P<0.000 01], WAB-listening comprehension score was significantly higher [MD=0.50, 95% CI (0.05,0.95)], Z=2.20, P=0.03], WAB-retelling score was significantly higher [MD=2.58,95% CI (2.18,2.98), Z=12.54, P<0.000 01] and WAB-naming score was significantly higher [MD=2.07, 95% CI (1.63, 2.50), Z=9.28, P<0.000 01]. (3) Picture naming test: compared with the control group, the score of picture naming test in the experimental group was higher [MD=23.17, 95% CI (10.11, 36.23), Z=3.48, P=0.000 5]. (4) CADL score: compared with the control group, the CADL score of the experimental group was higher [MD=15.08, 95% CI (10.88, 19.27), Z=7.05, P<0.000 01].ConclusiontDCS can effectively improve the communication ability of daily life, picture naming ability and language abilities of spontaneous language, listening comprehension, retelling and naming in patients with aphasia after stroke, with clinical efficacy and good safety. Due to the limitations of the included studies, high-quality, large-sample clinical randomized controlled trials are still needed in the further research to provide more reliable evidence-based basis.